THE EFFECTS OF ADDING SOY FIBER TO WHEAT SPAGHETTI - BENEDETTI-BORDIN, ALINE; ROQUE-SPECHT, VÂNIA FERREIRA (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2012)
This study has evaluated the effects of adding 4%, 6% and 8% soy fiber to wheat pasta for the production of dry wheat spaghetti. The properties of the mixture were evaluated for humidity, falling number, ashes, color, retained gluten, and subjected to farinograph (water absorption, development, stability) and extensograph analyses (resistance and extensibility). The spaghetti was evaluated with cooking tests (performance, increased volume, loss of soluble solids to cooking water) and sensory analysis. The addition of soy fiber to wheat flour resulted in mixtures with rheological and physicochemical characteristics suitable for the production of wheat spaghetti, enhancing performance and reducing the loss of soluble solids to the cooking water. The sensory analysis showed that, for all parameters tested, panelists favored mixtures with up to 6% soy fiber addition.